Political Muslims : understanding youth resistance in a global context - Abbas, Tahir, 1970-; Hamid, Sadek (Contemporary issues in the Middle East., 2019)
In "Political Muslims," Abbas, Hamid, and their contributors seek to provide a new perspective on Muslim youth, presenting them as agents of creative social change--as emerging adults who are participating in cultural, organizational, community, and socially oriented projects to positively influence socio-political transformation in response to the everyday challenges they face. Each case study brings the reader to a new geographic location, providing original contributions on how a new generation of Muslim youth are engaging in issues relating to their faith, gender, identity, community, social injustice, and globalization, and confronting social change and the negative impacts of Islamophobia and radicalization